Absolutul – „ultima frontieră” a cunoașterii - Liliana DANCIU (Eon, 2023)
In the volume of essays “The Absolute - from disintegration to reconstruction”, the theorist and thinker Mircea Braga starts from the considerations of the philosopher George Steiner about the “disintegration" of the old existential platform of humanity, based on a mythical knowledge of man and of the universe. The new existential platform absolutizes human reason and proclaims the “death of God," to promote social and ideological mythologies that promised earthly heaven. However, at the beginning of the 21st century, the Absolute is reconstructed with the help of science that ascertains the infinity of worlds that make up the universe. Neurosurgery proves the existence of the soul and quantum physics proclaims the validity of multiple worlds beyond the limits of our perception. Including the “world beyond"! The Absolute is “reconstructed", therefore, on scientific bases, consolidating itself both theoretically and spiritually. Mircea Braga captures the way of coagulation of the concept of the possible world in the prosaic and poetic, religious and analytical imaginary, by appealing to scientific studies and literary texts from the Romanian cultural space.